An Aluminum-coated sCMOS Sensor for X-Ray Astronomy - Wu, Qinyu; Ling, Zhixing; Zhang, Chen; Zhang, Shuang-Nan; Yuan, Weimin (Publications of the Astronomical Society of the Pacific, 2023)
In recent years, tremendous progress has been made on scientific Complementary Metal Oxide Semiconductor (sCMOS) sensors, making them a promising device for future space X-ray missions. We have customized a large-format sCMOS sensor, G1516BI, dedicated for X-ray applications. In this work, a 200 nm thick aluminum layer is successfully sputtered on the surface of this sensor. This Al-coated sensor, named EP4K, shows consistent performance with the uncoated version. The readout noise of the EP4K sensor is around 2.5 e − and the dark current is less than 0.01 e − pixel −1 s −1 at −30°C. The maximum frame rate is 20 Hz in the current design. The ratio of single pixel events of the sensor is 45.0%. The energy resolution can reach 153.2 eV at 4.51 keV and 174.2 eV at 5.90 keV at −30°C. The optical transmittance of the aluminum layer is approximately 10 −8 to 10 −10 for optical lights from 365 to 880 nm, corresponding to an effective aluminum thickness of around 140 to 160 nm. The good X-ray performance and low optical transmittance of this Al-coated sCMOS sensor make it a good choice for space X-ray missions. The Lobster Eye Imager for Astronomy, which has been working in orbit for about one year, is equipped with four EP4K sensors. Furthermore, 48 EP4K sensors are used on the Wide-field X-ray Telescope on the Einstein Probe satellite, which will be launched at the end of 2023.